Producing 3D printed high‐fidelity retroperitoneal models from in vivo patient data: The Oxford Method. Issue 6 (24th July 2020) - Williams, Matthew A.; Smillie, Robert W.; Richard, Michael; Cosker, Thomas D. A.
Abstract: Macroscopic anatomy has traditionally been taught using cadaveric material, lectures and a variable amount of additional resources such as online modules. Anatomical models have also been used to assist in teaching. Of these, traditional plastic models have been shown to be effective educational tools, yet have significant drawbacks such as a lack of anatomical detail and texturisation. Three‐dimensional (3D) printed models stand to solve these problems and widen access to high‐quality anatomical teaching. This paper outlines the use of 3D multi‐planar imaging (CT and MRI) as a framework to develop an accurate model of the retroperitoneum. CT and MRI scans were used to construct a virtual 3D model of the retroperitoneum. This was printed locally as a full‐size colour model for use in medical education. We give a complete account of the processes and software used. This study is amongst the first of a series in which we will document the newly formed Oxford Library of Anatomy . This series will provide the methodology for the production of models from CT and MRI scans, and the Oxford Library of Anatomy will provide a complete series of some of the most complex anatomical areas and ones which degrade quickly when a real cadaver is being used. In our own internal experience, the models are highly accurate, reproducible and durable, as compared to prosected specimens. We hope they will form an important adjunct in the teaching of the subject. Abstract : We outline the steps required to produce a high fidelity anatomical model from in vivo patient data, followed by a discussion of the advantages and disadvantages relative to current available options.